Single Nucleotide Polymorphisms (SNP) and SNP-SNP Interactions of the Surfactant Protein Genes Are Associated With Idiopathic Pulmonary Fibrosis in a Mexican Study Group; Comparison With Hypersensitivity Pneumonitis - Abbasi, Ata; Chen, Chixiang; Gandhi, Chintan K.; Wu, Rongling; Pardo, Annie; Selman, Moises; Floros, Joanna (Frontiers in Immunology, 2022)
Surfactant proteins (SPs) are important for normal lung function and innate immunity of the lungs. Changes in quantity or quality of SPs due to genetic alterations or natural genetic variability may alter their functions and contribute to the host susceptibility for particular diseases. In the current study, we evaluated associations of SFTP SNPs with idiopathic pulmonary fibrosis (IPF) using a new computational model for detecting epistatic effects (dominant, additive, recessive) of SNP-SNP interactions and compared the results with a previously published hypersensitivity pneumonitis (HP) study. Mexican Hispanic patients (IPF=84 & HP=75) and 194 healthy control individuals were evaluated. The goal was to find single nucleotide polymorphisms (SNPs) and SNP-SNP interactions that associate with IPF as well as those that may be unique to each of these interstitial diseases or common between them. We observed: 1) in terms of IPF, i) three single SFTPA1 SNPs to associate with decreased IPF risk, ii) three SFTPA1 haplotypes to associate with increased IPF risk, and iii) a number of three-SNP interactions to associate with IPF susceptibility. 2) Comparison of IPF and HP, i) three SFTPA1 and one SFTPB SNP associated with decreased risk in IPF but increased risk in HP, and one SFTPA1 SNP associated with decreased risk in both IPF and HP, ii) a number of three-SNP interactions with the same or different effect pattern associated with IPF and/or HP susceptibility, iii) one of the three-SNP interactions that involved SNPs of SFTPA1, SFTPA2, and SFTPD, with the same effect pattern, was associated with a disease-specific outcome, a decreased and increased risk in HP and IPF, respectively. These findings indicate that SNPs of all SFTPs appear to play an important role in the genetic susceptibility to IPF and HP, especially in the 3-SNP interactions, and these may contribute towards our ability to not only distinguish which may provide an example to start differentiating these two diseases based on their genetic backgrounbackground but also in decision-making for d.disease-specific therapies.